An Analysis of Work Stress and Family-Conflict Work on Organizational Commitment and Turnover Intention: A Case Study on Employee of PT. Apparel One Indonesia - Junaidi, Achmad; Elsa Adelia, Febri; Nindhita, Yoga (Jurnal Ilmiah Peuradeun, 2022)
This study departs from findings that show that the turnover rate of employees at PT. Apparel One Indonesia in 2018 is 3.715% which exceeds the threshold set by the company by 2% each year, and the findings that the variables that explain the phenomenon of turnover intention are still different which then leads to the formulation of the problem regarding "how to reduce turnover". Based on these problems, this study developed a research model that was empirically tested to re-explain the variables that could affect turnover intention by using data obtained from interviews using a questionnaire to PT. Apparel One Indonesia's employees. The test was conducted using the Structural Equation Modeling (SEM) approach. The test results showed that work stress and family conflict had a significant adverse effect on organizational commitment. This study also shows that work stress and work-family conflict had a significant positive effect on turnover intention. In contrast, organizational commitment had a significant negative effect on turnover intention.